Let's solve the equation \(2x - 5 = 3(4x + 5)\) by following the steps you provided.
Step 1: Distributive Property
First, we apply the distributive property on the right-hand side of the equation: \[ 3(4x + 5) = 3 \cdot 4x + 3 \cdot 5 = 12x + 15 \] So the equation becomes: \[ 2x - 5 = 12x + 15 \]
Step 2: Move variables to one side of the equation
Next, we want to move all the variable terms to one side of the equation. We’ll subtract \(12x\) from both sides: \[ 2x - 12x - 5 = 12x - 12x + 15 \] This simplifies to: \[ -10x - 5 = 15 \]
Step 3: Move constant to the other side of the equation
Now, we add \(5\) to both sides to isolate the variable term: \[ -10x - 5 + 5 = 15 + 5 \] This simplifies to: \[ -10x = 20 \]
Step 4: Isolate your variable
Finally, we want to isolate \(x\). We do this by dividing both sides by \(-10\): \[ \frac{-10x}{-10} = \frac{20}{-10} \] This simplifies to: \[ x = -2 \]
Thus, the solution to the equation \(2x - 5 = 3(4x + 5)\) is: \[ \boxed{-2} \]